Pharmacist to improve hypertension management: concordance between Europe and North America. (13th November 2019) - Anker, D; Tsuyuki, R T; Paradis, G; Chiolero, A; Santschi, V
Abstract: Problem: Hypertension is highly prevalent but remains poorly controlled, notably in European countries where control rates are frequently worse than in Canada and the United States. One innovative solution for improving hypertension management is team-based care (TBC) with the involvement of a pharmacist. Description of the problem: We systematically compared recommendations for TBC in hypertension management in recent European (ESC/ESH), American (ACC/AHA), and Canadian (Hypertension Canada) guidelines and pinpointed potential roles and responsibilities of pharmacists. Results: The three guidelines recommend TBC for the management of hypertension, with the ACC/AHA Guidelines giving a stronger emphasis by providing a more exhaustive definition of TBC and by describing the composition of the team. The three guidelines assign roles and responsibilities in hypertension management at the team level, but no firm role is defined for each specific team member. The three guidelines also refer to evidence showing that the pharmacist's involvement can embrace several activities, that is, diagnosis of hypertension, blood pressure monitoring, medication management, education of patient and health care providers, and communication and organization within the care team. Recent systematic reviews have shown that a pharmacist's involvement in these steps in hypertension management improves hypertension control compared to standard of care. Lessons: International guidelines, including European ones, recommend using TBC in hypertension management, based on strong evidence that a pharmacist's involvement improves hypertension control. Key messages: International guidelines recommend TBC and the involvement of pharmacists to improve hypertension management. Programs and policies to improve hypertension control in European countries should consider the involvement of pharmacists.